Human gut microbiota transferred to germ-free NOD mice modulate the progression towards type 1 diabetes regardless of the pace of beta cell function loss in the donor - Neuman, Vit; Cinek, Ondrej; Funda, David P; Hudcovic, Tomas; Golias, Jaroslav; Kramna, Lenka; Petruzelkova, Lenka; Pruhova, Stepanka; Sumnik, Zdenek (Diabetologia, 2019)
AIMS/HYPOTHESIS: This study aimed to assess the ability of human gut microbiota to delay the onset of type 1 diabetes when transferred into germ-free NOD mice. METHODS: Two children with rapid and three children with slow beta cell function loss (as assessed by C-peptide AUC change in the mixed-meal tolerance tests performed 1 and 12 months after type 1 diabetes onset), participating in an ongoing trial with gluten-free diet, donated faeces, which were transferred into germ-free NOD mice. The mice were subsequently followed for diabetes incidence. RESULTS: The bacterial profiles of bacteriome-humanised mice had significantly (p < 10-5) lower alpha diversity than the donor material, with marked shifts in ratios between the main phyla. Diabetes onset was significantly delayed in all bacteriome-humanised colonies vs germ-free NOD mice, but the pace of beta cell loss was not transferable to the mouse model. CONCLUSIONS/INTERPRETATION: Germ-free NOD mice colonised with human gut microbiome are able to adopt a large proportion of transferred bacterial content, although the ratios of main phyla are reproduced only suboptimally. The recipient mice did not replicate the phenotype of the stool donor in relation to the pace towards type 1 diabetes. TRIAL REGISTRATION: ClinicalTrials.gov NCT02867436.
Keywords: Gastrointestinal Microbiome; Feces; Human gut microbiome transfer; Germ-free NOD mice; Animals; myši inbrední NOD; Humans; Mice; Disease Progression; střevní mikroflóra; modely nemocí na zvířatech; mikrobiota; feces; zvířata; Diabetes Mellitus, Type 1; Mice, Inbred NOD; diabetes mellitus 1. typu; progrese nemoci; Type 1 diabetes; Microbiota; lidé; Disease Models, Animal; myši